2020
DOI: 10.1080/03088839.2020.1750720
|View full text |Cite
|
Sign up to set email alerts
|

The effects of safety delivery and safety awareness on passenger behaviour in the ferry context

Abstract: This research empirically examines passengers' perception of safety delivery and awareness on their preventative behaviours in the ferry context. Using survey data collected from 422 ferry passengers in Hong Kong, confirmatory factor analysis and structural equation modeling were conducted. An exploratory factor analysis identified two main dimensions of safety delivery, namely: safety facilities and safety demonstration. Safety awareness was further clustered into three dimensions, which included safety infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The statistical analysis packages SPSS and AMOS were used to perform CFA in order to evaluate the hypothetical model at the beginning of this study (Lau et al, 2021). We adopted several commonly used models to determine the fitness acceptance levels of the CoI theoretical framework, including chi-square to degrees of freedom (χ 2 /df), comparative fit index (CFI), and standardized root mean square residual (SRMR).…”
Section: Confirmatory Factor Analysis Modelmentioning
confidence: 99%
“…The statistical analysis packages SPSS and AMOS were used to perform CFA in order to evaluate the hypothetical model at the beginning of this study (Lau et al, 2021). We adopted several commonly used models to determine the fitness acceptance levels of the CoI theoretical framework, including chi-square to degrees of freedom (χ 2 /df), comparative fit index (CFI), and standardized root mean square residual (SRMR).…”
Section: Confirmatory Factor Analysis Modelmentioning
confidence: 99%
“…The concept of safety awareness draws from situational awareness, which refers to the perception of safety elements and potential hazards in a certain environment within a certain time and space, as well as a prediction of its future status (Korkmaz and Park, 2019;Lau et al, 2020;Uzuntarla et al, 2020). Lu et al (2018) used the data obtained from a survey of 316 ferry passengers in Hong Kong to conduct structural equation modelling, and studied the impact of safety marketing incentives on passengers' safety awareness and behaviour, and found that passengers' familiarity with the ship's environment affects their safety awareness, which in turn can positively affect passengers' behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lu et al (2018) used the data obtained from a survey of 316 ferry passengers in Hong Kong to conduct structural equation modelling, and studied the impact of safety marketing incentives on passengers' safety awareness and behaviour, and found that passengers' familiarity with the ship's environment affects their safety awareness, which in turn can positively affect passengers' behaviour. It was suggested that ferry operators should increase their attention to safety videos, guides and notices to increase their safety awareness of passengers (Lau et al, 2020;Lu et al, 2018). A survey study at the Melbourne Train Station by Shiwakoti et al (2016) found that many passengers did not have a clear understanding of wayfinding tools and evacuation processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maritime safety is closely related to ME proficiency [3]. Indeed, the International standard of ME is a means to improve safety in shipping [7] and minimize human error in ship operations [8]. The competence of ME as one of the human factors is of vital importance for maritime safety [9].…”
Section: Introductionmentioning
confidence: 99%